2020
DOI: 10.18632/aging.102894
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and validation of the prognostic value of the lncRNAs encoding snoRNAs in patients with clear cell renal cell carcinoma

Abstract: Some lncRNAs can encode small nucleolar RNAs (snoRNAs), called small nucleolar RNA host genes (SNHGs), which have exerted certain predictive values for the prognosis of some cancer patients. In this study, using RNA-seq and survival data in TCGA-KIRC, we examined the expression profile of 20 SNHGs and explored their prognostic values in ccRCC. Results showed that SNHG1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…With the study of the molecular mechanism of lncRNAs in tumors, lncRNAs may become new tumor biomarkers for the diagnosis and treatment of cancer targets [ 83 ]. Yang et al [ 84 ] used RNA-seq and survival data in the TCGA database to analyze the expression profiles of 20 SNHGs and discussed their prognostic value in clear cell renal cell carcinoma (ccRCC). Results of the study indicated that SNHG3 and SNHG15 act as diagnostic markers and indicators and may have great clinical value to evaluate the survival and progression of ccRCC.…”
Section: Perspectives In Clinical Practicementioning
confidence: 99%
“…With the study of the molecular mechanism of lncRNAs in tumors, lncRNAs may become new tumor biomarkers for the diagnosis and treatment of cancer targets [ 83 ]. Yang et al [ 84 ] used RNA-seq and survival data in the TCGA database to analyze the expression profiles of 20 SNHGs and discussed their prognostic value in clear cell renal cell carcinoma (ccRCC). Results of the study indicated that SNHG3 and SNHG15 act as diagnostic markers and indicators and may have great clinical value to evaluate the survival and progression of ccRCC.…”
Section: Perspectives In Clinical Practicementioning
confidence: 99%
“…20 Some researchers have reported the upregulated expression of SNHG22 in EOC, PTC, and ccRCC, and whose expression indicated poor prognosis in the three types of human malignancies. [11][12][13] In this study, we rst explored the expression patterns of SNHG22 in ANT, CRA, and CRC tissues, and found that SNHG22 expression was gradually upregulated in ANTs, CRA, and TTs. The high expression level of SNHG22 was associated with advanced T stage, node involvement, metastasis, and poor survival in CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…11 SNHG22 was then determined to be highly expressed in PTC and ccRCC. 12,13 We also checked the effects of SNHG22 on cell phenotype of CRC. We did prove that SNHG22 could promote cell proliferation, invasion, migration, and inhibit cell apoptosis of CRC in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small nucleolar RNA host gene 17 (SNHG17) was reported to accelerate cell proliferation and invasion in castrationresistant prostate cancer (CRPC) by targeting the miR-144/CD51 axis [20]. Furthermore, as lncRNAs that encode small nucleolar RNAs (snoRNAs), the prognostic value of SNHG17 and SNHG15 in KIRC patients has been investigated, and DNA hypomethylation might play a key role in elevated SNHG15 transcription in KIRC [21]. Recently, AC026356.2 and MELTF-AS1 were identi ed as immune-related lncRNA and showed a signi cant relationship with KIRC prognosis [22].…”
Section: Discussionmentioning
confidence: 99%